Correction: Simple hydrothermal synthesis of mesoporous spinel NiCo2O4 nanoparticles and their catalytic behavior in CH3OH electro-oxidation and H2O2 electro-reduction. Issue 6 (27th June 2015) - Ding, Rui; Qi, Li; Jia, Mingjun; Wang, Hongyu
<x xml:space="preserve">Abstract</x> Correction for 'Simple hydrothermal synthesis of mesoporous spinel NiCo2O4 nanoparticles and their catalytic behavior in CH3OH electro-oxidation and H2O2 electro-reduction' by Rui Ding et al., Catal. Sci. Technol., 2013, 3, 3207–3215.